The Impact of Toll Road Development on Urbanization Typology and Economic Structure (Case Study: Palikanci Toll Road in Ciledug District, Cirebon Regency) - Hasyim, Muhammad Fuad; Widjaja, Arni Muslimah Handayani; Alamsyah, Fichri Surya; Qira‘ati, Muhfidlatul (Journal of World Science, 2024)
This study examines the impact of toll roads on regional growth, specifically focusing on the Ciledug District, which has been crossed by the Palikanci Toll Road since 2009. The research identifies the typology of urbanization and assesses changes in the area’s economic structure due to the toll road. A mixed method approach was used, combining qualitative and quantitative data collection, land change analysis via Google Earth and ArcGis 13.1, and field observations of land use. The findings reveal gentrification in the northern part of Ciledug, marked by the growth of business centers in Jatiseeng and rising land prices. This has led to the expansion of settlements toward the southern area, particularly in Jatiseeng Kidul. The toll road and the industrial estate in North Ciledug have accelerated the transformation of the local economy, with residents diversifying their livelihoods to adapt to urbanization. However, the study also notes a lack of improvement in essential infrastructure services, suggesting that regional development policies have not yet adapted to the gentrification, posing risks of urban sprawl.